2016
DOI: 10.1097/ccm.0000000000001959
|View full text |Cite
|
Sign up to set email alerts
|

The Role of κ Opioid Receptor in Brain Ischemia

Abstract: Objectives Our previous studies indicated that highly selective kappa opioid receptor (KOR) agonists could protect the brain, indicating an important role of KOR agonist in brain ischemia. In this study, we investigated the role and related mechanisms of KOR agonists in brain ischemia in a middle cerebral artery occlusion (MCAO) mouse model. Subjects and Interventions The MCAO model was established by 120 minutes of ischemia followed by 24 h reperfusion in male adult mice. Various doses of salvinorin A (SA),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 27 publications
(32 reference statements)
1
29
0
Order By: Relevance
“…The main active constituent isolated from the leaves of S. divinorum is the neoclerodane diterpene salvinorin A, which has shown reduced infarct volume and improved neurological deficits. It also reduced Evans blue extravasation, suggesting reduced impairment of the blood-brain barrier, and decreased the expression of cleaved casepase-3, IL-10, and TNF-alpha in the penumbral areas, preventing apoptosis and reducing inflammation [27]. Thus, our results suggest that extracts from Lamiaceae could be an alternative for treating cerebral ischemia, but it will be necessary to characterize the components of the extract; that is, the identification and evaluation of the active compounds will be required to elucidate its mechanism of action in the induced protection against cerebral ischemia…”
Section: Sp Extract Protects Against Cerebral Ischemia-induced Damagementioning
confidence: 93%
See 1 more Smart Citation
“…The main active constituent isolated from the leaves of S. divinorum is the neoclerodane diterpene salvinorin A, which has shown reduced infarct volume and improved neurological deficits. It also reduced Evans blue extravasation, suggesting reduced impairment of the blood-brain barrier, and decreased the expression of cleaved casepase-3, IL-10, and TNF-alpha in the penumbral areas, preventing apoptosis and reducing inflammation [27]. Thus, our results suggest that extracts from Lamiaceae could be an alternative for treating cerebral ischemia, but it will be necessary to characterize the components of the extract; that is, the identification and evaluation of the active compounds will be required to elucidate its mechanism of action in the induced protection against cerebral ischemia…”
Section: Sp Extract Protects Against Cerebral Ischemia-induced Damagementioning
confidence: 93%
“…The bioactive clerodane diterpenes are abundant in both species [26]. Clerodanes can be used to activate opioid receptors and protect against cerebral ischemia [27].…”
Section: Introductionmentioning
confidence: 99%
“…The indirect evidence for such statement is that SA, the highly selectively KOR agonist, can induce KOR internalization similar to that by hypoxia and SA could protect the brain from hypoxia and ischemia, resulting improved neurological outcome as we have demonstrated in a rodent model of brain ischemia. 48 Further experiments are needed to investigate whether naïve KORs in primary neuronal cultures undergo similar trafficking as in neuroblastoma cells with KOR over-expression.…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of AQP‐4 was associated with brain edema, and its expression in brain peaks at 24‐72 hour post–brain injury, which coincides with brain edema development . Salvinorin A (SA) is a selective kappa opioid receptor (KOR) agonist, which could dilate the pial artery with high potency and maintain the cerebral autoregulation . Highly lipophilic structure of SA allows it to diffuse through the blood‐brain barrier easily .…”
Section: Introductionmentioning
confidence: 99%
“…14 Salvinorin A (SA) is a selective kappa opioid receptor (KOR) agonist, which could dilate the pial artery with high potency and maintain the cerebral autoregulation. 15,16 Highly lipophilic structure of SA allows it to diffuse through the blood-brain barrier easily. 17,18 We have demonstrated that SA can preserve cerebrovascular autoregulatory ability after hypoxia/ischemia 19 and dilate pial arteries via activation of nitric oxide synthase (NOS).…”
Section: Introductionmentioning
confidence: 99%